Surface heat treatment method of metal products
By first performing solid solution chromium permeation on the surface of metal products and adopting slow cooling, then performing solid solution nitriding and using quench cooling, the problems of low surface treatment efficiency and unstable quality of metal products in the prior art are solved, and high efficiency is achieved , high-speed seepage layer is formed.
Patent Information
- Application Number
- CN202111368569.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-18
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-11-18
AI Technical Summary
In the prior art, the surface chromium and nitriding treatment of metal products have problems of low efficiency and unstable treatment quality, especially on austenitic stainless steel, the thickness of the nitriding layer is difficult to achieve and the time is long.
A surface heat treatment method for metal products is adopted, and the surface chromium chromium filtration step is performed first. The chromium filtration stage is carried out at the solid solution temperature and adopts slow cooling and cooling; then the surface nitriding step is carried out, and the nitriding stage is carried out at the solid solution temperature and adopts rapid cooling. Cool down. This method improves the depth and hardness of the seepage layer by adjusting the cooling method and the sequence of process steps.
It is possible to obtain a high-quality seepage layer in a short time, especially on austenitic stainless steel. The thickness of the nitriding layer can reach 70 μm to 110 μm, which significantly improves the heat treatment efficiency and treatment quality.
Smart Images

Figure BDA0003361776470000151 
Figure BDA0003361776470000152 
Figure BDA0003361776470000161
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal product surface treatment, in particular to a metal product surface heat treatment method. Background Art
[0002] In the prior art, chromizing and nitriding the surface of metal products are common surface treatment technologies for metal products.
[0003] Chromizing is a surface chemical heat treatment process that infuses chromium into the surface of metal parts. Common chromizing methods include filler embedding (also known as solid or powder methods), gas methods, molten salt methods (also known as liquid methods), vacuum methods, electrostatic spraying, or thermal diffusion methods. Chromizing high-temperature alloys can improve their resistance to oxidation, high-temperature hot corrosion, and low-temperature hot corrosion.
[0004] Gas nitriding is a common surface treatment method for metal products. This involves placing the workpiece in a sealed heating furnace and introducing a nitrogen-containing gas (typically ammonia) at a certain pressure for a period of time. The goal of gas nitriding is to form a nitrided layer on the workpiece surface that exhibits high hardness, wear resistance, pitting resistance, improved fatigue life, and enhanced resistance to atmospheric and halogen corrosion.
[0005] In the prior art, solid chromizing is a process for chromizing metal products. The chromizing powder is generally composed of chromium powder and a chromizing agent. For example, vacuum chromizing is performed in a vacuum furnace at a vacuum degree of 0.133 Pa, with a typical temperature of 1100-1150°C. The holding time depends on the required chromized layer thickness.
[0006] At the same time, in addition to the separate nitriding and chromizing processes, the existing technology also includes a surface heat treatment process for metal products using chromium-nitrogen co-diffusion.
[0007] Further optimization of the surface treatment process of metal parts will undoubtedly promote the further development of the manufacturing industry. Summary of the Invention
[0008] To address the aforementioned technical challenges of further optimizing the surface treatment process for metal parts, which will undoubtedly advance the manufacturing industry, the present invention provides a method for surface heat treatment of metal products. The technical solution proposed in this proposal effectively ensures the quality of surface heat treatment of austenitic stainless steel parts.
[0009] In response to the above problems, the present invention provides a metal product surface heat treatment method and processing method to solve the problem through the following technical points: the metal product surface heat treatment method includes a surface nitriding step and a surface chromizing step of the metal product, wherein the surface chromizing step is located before the surface nitriding step;
[0010] In the surface chromizing step, the chromizing stage includes a solution chromizing stage in which chromizing is performed at a solution temperature of the metal product. After the solution chromizing stage is completed, a slow cooling method is adopted in the cooling process of the metal product.
[0011] In the surface nitriding step, the nitriding stage includes a solid solution nitriding stage in which nitriding is performed at the solid solution temperature of the metal product. After the solid solution nitriding stage is completed, a rapid cooling method is adopted in the cooling process of the metal product.
[0012] As those skilled in the art know, in the above two steps, in terms of the order of front and back, the above chromizing treatment is the pre-treatment performed on the surface of the metal product, and the above nitriding treatment is the post-treatment performed on the surface of the metal product.
[0013] This solution is applicable to stainless steel that requires surface chromizing and nitriding treatment, and is more significant when applied to austenitic stainless steel.
[0014] In this scheme, the solid solution chromizing stage is the stage in which the metal product is chromized at the solid solution temperature, which aims to take advantage of the active ion exchange between the product substrate elements and the chromizing agent metal elements to quickly obtain the required penetration layer depth (in fact, chromizing does not only occur at the solid solution temperature); the solid solution nitriding is the nitriding of the metal product at the solid solution temperature. Taking stainless steel metal products as an example, according to the principle of thermal diffusion, the diffusion rate is proportional to the temperature. The solid solution temperature of stainless steel is mostly above 950°C. Heating the metal product to the solid solution temperature can effectively increase the diffusion rate of nitrogen. Further, taking austenitic stainless steel as an example, unlike the nitriding of traditional iron-based materials, nitriding is relatively difficult. In addition to considering that the stainless steel surface is very easy to produce a passive film that hinders the nitriding process, the stainless steel itself has a high content of Cr and Ni (strong nitride-forming elements). Under conventional nitriding methods, it takes longer to achieve a certain penetration layer thickness. Experiments have shown that using this solution, a nitrided layer thickness of 70μm to 110μm can be achieved on common austenitic stainless steel after 5 hours of solid solution nitriding. Conventional nitriding methods often require more than 80 hours to achieve this thickness. This solution provides a technical solution that ensures heat treatment efficiency.
[0015] At the same time, this solution aims to provide a technical solution that can effectively ensure the quality of surface heat treatment of austenitic stainless steel metal products. In the specific process steps designed in this solution, the surface chromizing step is set to be located before the surface nitriding step, and the surface chromizing step adopts slow cooling, while the surface nitriding step adopts rapid cooling. After the chromizing step is completed, slow cooling is preferably used: During the specific chromizing process, the product parts are in a solid solution state and at a high temperature. If the cooling rate is too fast, there are hidden dangers such as excessive stress in the chromized layer causing cracking and falling off. There is also a risk that the internal air pressure changes due to the rapid cooling rate, which may eventually increase the adhesion of powder and have an adverse effect on the part size. However, when slow cooling is implemented, conventional austenitic stainless steel is prone to intergranular corrosion. Therefore, this solution sets the nitriding step to be located after the chromizing step. By placing the chromized stainless steel at the solid solution temperature of the surface nitriding step, this harmful tendency can be effectively eliminated. Then, a rapid cooling method is adopted. While ensuring that the substrate does not have the tendency to intergranular corrosion, the rapid cooling can also effectively improve the hardness of the nitrided layer and prevent the hardness of the nitrided layer from decreasing due to the long-term maintenance of the solid solution temperature.
[0016] As a further technical solution of the metal product surface heat treatment method:
[0017] As a more specific application of the treatment method on austenitic stainless steel metal products, it is set as follows: the material of the metal product is austenitic stainless steel;
[0018] In the surface nitriding step, after the rapid cooling is completed, the temperature of the metal product is less than or equal to 400° C.
[0019] The slow cooling has a cooling rate of 30-35°C / h;
[0020] The cooling rate of the rapid cooling is 300-500℃ / h. In this solution, the temperature of the metal product at the end of rapid cooling is limited in order to shorten the duration of the intergranular corrosion sensitive temperature zone of austenitic stainless steel by rapid cooling, so as to ensure the structural composition of the surface nitride as much as possible (avoid nitrogen loss and structural changes), thereby ensuring the surface performance of the product. It is preferably set so that the metal product has a temperature below 200℃ after the rapid cooling is completed, so as to avoid oxidation or reduce the degree of oxidation during subsequent cooling in an open environment. The above-set slow cooling rate is a compromise between protecting the chromized layer, cooling efficiency, and intergranular corrosion tendency; the above rapid cooling rate is a compromise between protecting the chromized layer and cooling efficiency.
[0021] In existing nitriding processes, ammonia is often used as the nitrogen-containing gas. However, this solution takes into account the following considerations: According to general nitriding rules, to ensure the nitriding treatment results (achieve high-precision nitriding control), the chemical potential of nitrogen in the nitriding atmosphere must be controlled. This is because general "gas-solid" interface nitriding requires a fixed nitrogen chemical potential on the product surface, which means that the composition inside the nitriding vessel should not change compared to the desired inlet gas composition. However, this solution requires nitriding at the solid solution temperature. In reality, ammonia will completely decompose at a pressure of 1 atm and a temperature above 350°C. The nitriding gas pressure used in this process and the solid solution temperature of stainless steel nitriding (far exceeding 350°C) determine that it is impossible to use ammonia for controllable nitriding. (If ammonia is used for nitriding, it will completely decompose in the heat and pressure environment of this process, and the nitrogen potential will decrease linearly as the nitriding progresses.) In other words, if ammonia is used for nitriding, it is impossible to accurately control the size of the nitrided layer and the uniformity of nitrogen diffusion on the product surface, which in turn affects the performance of the product.
[0022] Therefore, it is set as follows: in the surface nitriding step, the nitriding gas used is nitrogen. Using nitrogen will not cause the above problems: nitrogen will only decompose into free nitrogen atoms N under high temperature and high pressure conditions. ads , and then dissolves into the solid solution matrix (N ads →[N]), affected by the diffusion rate of the “gas-solid” interface, the excess N ads It will be recombined and absorbed on the surface of metal products, that is, the reverse effect of nitriding occurs (N ads +[N]→N2). It is precisely because of this counteraction (dynamic equilibrium) that the composition inside the nitriding vessel is virtually unchanged from the desired inlet gas composition, thereby ensuring nitriding quality. Furthermore, the diffusion rate of nitrogen in stainless steel is low. To achieve sufficient nitriding depth within an appropriate timeframe, this solution utilizes a solution temperature range. Within this temperature range, the nitrogen decomposition rate is extremely high, achieving equilibrium between the gas phase and the nitrogen dissolved into the surface during the dissolution process, resulting in an extremely high surface nitride content (≥99%).
[0023] As a further preferred embodiment of the above-mentioned nitrogen, it is set as follows: the purity of the nitrogen is greater than or equal to 99%. The nitrogen content in ordinary industrial nitrogen components is generally 92%, and the remaining components are mainly composed of O2, CO2, H2O, H2, SO2, etc. When industrial nitrogen is used for nitriding, oxidation and sulfidation may occur simultaneously. Among them, oxidation is the most dangerous because oxidation will cause the loss of chromium and nickel on the surface of metal products, which will have a negative impact on the corrosion resistance of stainless steel and even cause the metal products to be scrapped; while sulfidation will reduce the alloying elements on the surface of metal products, increase the brittleness of the surface after nitriding, and reduce its corrosion resistance. When nitriding is carried out using process nitrogen with a nitrogen component of 92%, the structure of the nitrided layer is observed under a metallographic microscope, and it is found that the surface nitrided layer has uneven granular structures, and the outer surface of the metal product is dark in color; under the measurement of a microhardness tester, the surface hardness is low, and a green oxidation color will appear locally. Using high-purity nitrogen with a nitrogen content of 99% or higher for nitriding under the same process results in a fine and uniform surface structure, a silver-gray surface color, and high surface hardness. This effectively avoids adverse effects such as oxidation and sulfidation. Furthermore, high-purity nitrogen promotes the structural transformation of metal products in the α phase due to nitrogen supersaturation, forming the γ phase, which improves surface hardness. Considering nitrogen cost and heat treatment quality, high-purity nitrogen with a nitrogen content of 99.999% is preferred.
[0024] The material of the metal product is austenitic stainless steel;
[0025] In the surface chromizing step, chromium powder with a chromium content greater than or equal to 99% is used as a chromium supplying agent in the chromizing agent. In the prior art, the metal product is subjected to solution chromizing heat treatment by completing chromizing at the solution temperature, and the components of the chromizing agent generally include a chromium supplying agent, a filler, and a penetration promoter. Regarding the chromizing agent, the options include chromium powder, chromium oxide, ferrochrome powder, or any two or a mixture of the above three. From the perspective of the quality of the diffusion layer, chromium oxide and ferrochrome powder not only have higher impurity content (such as high carbon and silicon content in ferrochrome powder, impurities in chromium oxide generally include silicon oxide, carbon impurities accompanying the solution heat treatment of metal products will affect the corrosion resistance of the austenitic stainless steel surface, silicon is a ferrite-forming element, accompanying the solution heat treatment of metal products will affect the intergranular corrosion sensitivity of the austenitic stainless steel surface), but also affect the chromizing quality; compared with chromium powder, ferrochrome powder and chromium oxide generally have shallower diffusion layers and lower density under the same chromizing process.
[0026] In response to the above-mentioned problems, this solution, in combination with the component characteristics or material characteristics of austenitic stainless steel, provides a technical solution for using chromium powder as a chromium supply agent during the chromizing process of austenitic stainless steel, and is limited to: the chromium content in the chromium powder is greater than or equal to 99% (for those skilled in the art, this 99% is the mass fraction of chromium element: the proportion of chromium in the mass of the chromium powder). The technical solution aims to solve the following problems:
[0027] First, in the actual chromizing process, to control production costs, inert fillers (fillers) such as alumina are often used to increase the volume of the metal product so that the chromizing agent can embed itself within the metal. The quality of the halogen salt activator (penetration promoter) and the chromium powder (chromium supply agent) required to achieve the technical requirements for the chromizing layer must be carefully calculated. Too much activator can cause localized surface corrosion, similar to "mottling" on the metal surface; too little activator can lead to deviations in the thickness of the chromized layer, or even fail to meet technical requirements. The purity of the chromium powder actually affects the amount of chromium, so higher purity chromium powder facilitates precise control of the chromium content.
[0028] Secondly, chromium powders currently available on the market with a chromium content of 99% or less generally contain ferrite-forming elements such as titanium, niobium, molybdenum, and silicon. However, during the chromizing of austenitic stainless steel, since austenitic stainless steel itself contains ferrite-forming elements, the matrix easily forms a σ phase during the solid solution process. When the σ phase precipitates along the grain boundaries of austenitic stainless steel, it significantly affects the plasticity of the steel. Furthermore, since the σ phase in chromium-nickel austenitic stainless steel is a chromium-iron intermetallic compound with a high chromium content, when it forms at the grain boundaries, it also forms a certain chromium-depleted zone around it. This can cause localized intergranular corrosion in corrosive media, especially in the strongly oxidizing medium produced by the decomposition of the activator during the solid solution chromizing process. This intergranular corrosion sensitivity is even more pronounced, making the material particularly susceptible to pitting corrosion in Cl-containing media. In this solution, by selecting the chromium supply agent and using higher purity chromium powder, the infiltration of non-chromium elements during the chromizing process can be effectively reduced. By increasing the chromium content of the infiltrating elements in the steel, the purpose of reducing the impact of this intergranular corrosion on austenitic stainless steel is achieved.
[0029] Finally: If you choose chromium powder with a purity of 99.9-99.99% (mass fraction of chromium), you can keep the ferrite content in the normal austenitic stainless steel between 5-20%, which is beneficial for resisting intergranular corrosion. During the chromizing process, if the ferrite-forming element content in the chromizing agent is high, the ferrite-forming elements can diffuse into the metal products at high temperatures, affecting the value of this range to some extent.
[0030] The chromizing agent also includes a penetration enhancer, which is a mixture of ammonium chloride and ammonium iodide;
[0031] The mass of the permeation promoter accounts for 1-4% of the mass of the chromizing agent. Regarding the selection of the above permeation promoter, if only NH4I is used as the activator, since I- is less oxidizing than Cl-, its reaction ability with Cr element is limited, resulting in an uneven chromizing layer or even no chromizing layer in some parts;
[0032] If only NH4Cl is used as the chromizing agent, Cl- has strong oxidizing properties and is more reactive with Cr elements. However, it is found that the surfaces of metal products of different sizes produced by the furnace all have mottled patterns. Observation under a metallographic microscope shows that surface corrosion may have occurred, and the thickness of the chromized layer at the mottled pattern is significantly lower than that at the normal chromized area. The hardness of the mottled pattern and the normal chromized layer are measured using a microhardness tester, and it is found that there is a large gap between the two (the hardness and chemical composition of the mottled pattern are quite different from those of the normal chromized area, and the normal area has a HV 0.1 ≥1200, HV at the site of spotting 0.1 The temperature is generally around 800°C. Considering that the decomposition products of NH4Cl promote localized corrosion on the surface of metal products while promoting penetration, using only NH4I results in a thinner chromized layer at the same time, making it more difficult to promote penetration than using NH4Cl. Achieving the same chromized layer thickness requires a longer heating time, which can cause grain growth within the metal product and deteriorate its performance. Using a mixture of NH4Cl and NH4I as a penetration promoter can produce a more ideal chromized layer than using a single penetration promoter.
[0033] The proportion of the mass of the penetration promoter in the mass of the chromizing agent is set to limit the amount of halogen ions to ensure the quality of chromizing: it can effectively promote chromizing and will not damage the surface of the metal product due to excessive strong oxidizing halogen ions.
[0034] The components of the penetration enhancer are set as follows: the weight ratio of ammonium chloride to ammonium iodide in the penetration enhancer is (1.5-2.5):1. The above limitation on the weight ratio of the components in the penetration enhancer is intended to address the following concept: regarding compound stability, NH4Cl < NH4I, that is, in the early preheating stage of the chromizing temperature curve (such as before the second gradient section mentioned below), NH4Cl almost completely decomposes (NH4Cl almost completely decomposes at 337°C) into HCl + NH3 (both in the gas phase), and this decomposition reaction is reversible. In contrast, the decomposition products of NH4I are NH3, H2, and I2 (in the vapor phase), which is an irreversible reaction. The use of NH4Cl decomposition products in the early stage will inhibit the decomposition of NH4I. This not only ensures that NH4I can be completely decomposed later after the decomposition of NH4Cl is complete, but also avoids insufficient penetration enhancer: the chromizing reaction occurs not only on the surface of the metal product, but also on the inner surface of the chromizing container. The suppression of NH4I decomposition in the early stage ensures that there are sufficient halide ions in the atmosphere of the chromizing surface later. At the same time, the decomposition product of NH4Cl, HCl, can remove the passivation film and promote penetration through reaction.
[0035] The ratio of NH4Cl and NH4I is (1.5-2.5):1, which aims to ensure that there are sufficient halogen ions to promote the diffusion in the preheating stage and the high-temperature solid solution stage, so as to ensure that the thickness of the diffusion layer and the Cr content in the Cr diffusion layer are high enough: the actual chromization occurs at various moments of the temperature gradient curve, and the specific chromization locations include the inner wall of the chromization container, tooling and metal products. NH4Cl mainly supplies the chromization in the front part of the temperature gradient curve, and NH4I mainly supplies the halogen ions in the high-temperature zone in the back part of the temperature gradient curve. In the high-temperature stage, the Cr concentration on the chromized surface of the metal product is greater than the critical Cr concentration for the generation of only Cr2O3 (such as the Cr concentration is 10% in the range of 850℃-1050℃). The Cr concentration near the outer surface of the metal product is higher than that in the interior of the matrix, and the Cr element diffuses deeply. A combination of NH4Cl and NH4I in a ratio of (1.5-2.5):1 is selected for chromization. Taking advantage of the characteristics that the higher the temperature of I element, the greater the diffusion coefficient of chromization is and that it basically does not damage the surface of metal products, the chromization temperature can be increased to an upper limit of about 1150°C in order to obtain a chromized layer of sufficient size, a chromized layer with a higher chromium content, and a relatively short chromizing time.
[0036] In the ratio range of NH4Cl and NH4I, parameters such as 1:2, 1:1, 1.5:1, 2:1, 2.5:1, and 3:1 were selected. It was found that the chromized layers with ratios of 1:1, 1:2, and 3:1 became rough and uneven, with large differences in thickness and surface defects such as mottled patterns. Therefore, in order to improve the quality of chromizing, the ratio of NH4Cl:NH4I=(1.5~2.5):1 was adopted.
[0037] For better effect, the weight ratio of ammonium chloride to ammonium iodide is set to (1.8-2.1):1.
[0038] To reduce the effects of silicon, iron, and other elements on the surface of metal products, the chromizing agent also includes a filler, which is aluminum powder, aluminum oxide powder, or a mixture of aluminum and aluminum oxide powders, with a purity greater than or equal to 99%. Specifically, in practice, the filler may be aluminum powder alone, aluminum oxide powder alone, or a mixture of aluminum and aluminum oxide powders.
[0039] The specific chromizing agent composition can be: 99.99% high-purity chromium powder (45% to 70%), 99% high-purity alumina powder (30% to 55%), NH4Cl and NH4I mixed activator (1% to 4%), and sodium fluoride (0.5% to 1.5%), which are evenly mixed.
[0040] In both the surface chromizing step and the surface nitriding step, a heating method of performing gradient heating and gradient section heat preservation on the metal product is adopted.
[0041] In the above chromizing steps, a gradient temperature increase method is adopted to improve the quality of chromizing: for example, during the insulation process of the gradient section, not only the base temperature of the metal product is increased, but also the moisture on the surface of the metal product and in the chromizing agent is removed by drying, thereby preventing the subsequent decomposition products of the activator from causing acidic corrosion to the surface of the metal product; the activator is completely decomposed to release activated gas, and the residual air around the metal product and in the chromizing agent is removed to avoid oxidation of the metal product; at the subsequent solution chromizing temperature (due to the previous insulation, the temperature difference between the inside and outside of the metal product is smaller or the temperature is the same, and the time required for the chromized surface to be heated to the solution temperature is shorter), the relevant element replacement reaction can be carried out in the first time, thereby improving the chromizing efficiency and reducing the solution chromizing time, thereby reducing to a certain extent the adverse effects of grain growth caused by long-term solution.
[0042] In the above nitriding steps, gradient heating and heat preservation are adopted mainly because the heating of metal products is mainly carried out through secondary thermal radiation (such as: the first is heating furnace-air-tooling (nitriding container), and the second is: tooling-nitrogen-metal product). The heat transfer process causes a certain error between the temperature of the metal product and the temperature displayed by measuring instruments such as furnace thermocouples during heating. Therefore, one of the purposes of heat preservation after heating is to increase the base temperature of the metal product to facilitate nitrogen activation at the subsequent solution temperature: the relevant element replacement reaction at the solution temperature can be carried out at the first time, thereby improving the nitriding efficiency, reducing the solution time, and effectively avoiding the problem of poor performance of the nitriding layer caused by excessive grain growth and poor grain uniformity due to excessive solution time.
[0043] More specifically, in the surface chromizing step, the holding section in the heating curve includes a third gradient section and a fourth gradient section; preferably, the holding section also includes the first gradient section and the second gradient section provided before the first gradient section, and specifically, in chronological order:
[0044] The temperature of the first gradient section is 280-320°C;
[0045] The temperature value of the second gradient section is 550-650°C;
[0046] The temperature value of the third gradient section is 900-950°C;
[0047] The temperature value of the fourth gradient section is 1050-1150°C;
[0048] In the surface nitriding step, the holding section in the heating curve includes the seventh gradient section and the eighth gradient section; preferably, it is set to also include the fifth gradient section and the sixth gradient section arranged before, specifically in chronological order:
[0049] The temperature value of the fifth gradient section is 280-350°C;
[0050] The temperature value of the sixth gradient section is 500-650°C;
[0051] The temperature of the seventh gradient section is 850-980°C;
[0052] The temperature value of the eighth gradient section is 1000-1150°C.
[0053] In the above nitriding step scheme, the typical process can be to slowly heat up to 280℃~300℃, keep warm for 1~3h → heat up to 550℃~620℃, keep warm for 1~3h → heat up to 900℃~950℃, keep warm for 0.5~1h → keep warm at 1030℃~1100℃ for 3~6h (determined by the thickness requirement of the nitriding layer) → quickly cool to 200℃.
[0054] In the above chromizing step scheme, in addition to further increasing the base temperature of the metal product at each stage, the first gradient stage is the stage of drying the metal product and the chromizing agent; the second gradient stage is the stage of complete decomposition of the activator; and the third gradient stage is intended to achieve:
[0055] 1. Stabilization of the base material of metal products: After heating to 900-950℃ and keeping it at 900-950℃, the C remaining in the austenite can fully react with Ti, Nb, etc. and precipitate in the form of TiC and NiC, so that C cannot form Cr precipitation along the grain boundary with Cr in the subsequent fourth gradient section. 23 C6 carbide can prevent intergranular corrosion in subsequent processes.
[0056] 2. Improve the temperature uniformity of the base material, reduce the temperature difference between the core and outer surface of the metal product and the heating furnace temperature (the heating furnace is used to heat the chromizing container), and reduce the time it takes for the metal product to reach the chromizing temperature due to multiple heat transfers: the heating time from the end of the third gradient section to the fourth gradient section; the time difference between the chromized surfaces at different positions or the chromized surfaces at different positions reaching the solid solution temperature, to ensure that the quality of the chromized layer is accurately controllable.
[0057] In this scheme, the fourth gradient section is the solid solution chromizing temperature stage, which is used to complete chromizing at the austenite solid solution temperature. The temperature range of 1050-1150℃ is used for insulation. The ion exchange between the base material elements and the metal elements of the chromizing agent is active, which can ensure the depth of the diffusion layer.
[0058] The present invention has the following beneficial effects:
[0059] Compared with the existing technology, the surface chromizing and nitriding of metal products can be carried out efficiently and with high quality at the solid solution temperature. The more prominent and significant feature is that in the specific process steps designed in this scheme, the surface chromizing step is set before the surface nitriding step, and the surface chromizing step adopts slow cooling, and the surface nitriding step adopts rapid cooling. After the chromizing is completed, slow cooling is preferably adopted: in the specific chromizing process, the product parts are in a solid solution state and at a high temperature. If the cooling rate is too fast, there are hidden dangers such as excessive stress in the chromized layer causing cracking and falling off, and there is a risk of internal air pressure changes due to the excessive cooling rate, which may eventually increase powder attachment and have an adverse effect on the size of the parts. However, when slow cooling is implemented, conventional austenitic stainless steel is prone to intergranular corrosion. Therefore, this solution sets the nitriding step after the chromizing step. By placing the chromized stainless steel at the solution temperature of the surface nitriding step, this harmful tendency can be effectively eliminated. The rapid cooling method is then adopted. While ensuring that the substrate does not have a tendency to intergranular corrosion, the rapid cooling can also effectively increase the hardness of the nitrided layer and prevent the hardness of the nitrided layer from decreasing due to maintaining the solution temperature for too long. DETAILED DESCRIPTION
[0060] The present invention will be further described in detail below with reference to the embodiments, but the present invention is not limited to the following embodiments:
[0061] Example 1:
[0062] A surface heat treatment method for a metal product, comprising a surface nitriding step and a surface chromizing step for the metal product, wherein the surface chromizing step is located before the surface nitriding step;
[0063] In the surface chromizing step, the chromizing stage includes a solution chromizing stage in which chromizing is performed at a solution temperature of the metal product. After the solution chromizing stage is completed, a slow cooling method is adopted in the cooling process of the metal product.
[0064] In the surface nitriding step, the nitriding stage includes a solid solution nitriding stage in which nitriding is performed at the solid solution temperature of the metal product. After the solid solution nitriding stage is completed, a rapid cooling method is adopted in the cooling process of the metal product.
[0065] As those skilled in the art know, in the above two steps, in terms of the order of front and back, the above chromizing treatment is the pre-treatment performed on the surface of the metal product, and the above nitriding treatment is the post-treatment performed on the surface of the metal product.
[0066] This solution is applicable to stainless steel that requires surface chromizing and nitriding treatment, and is more significant when applied to austenitic stainless steel.
[0067] In this scheme, the solid solution chromizing stage is the stage in which the metal product is chromized at the solid solution temperature, which aims to take advantage of the active ion exchange between the product substrate elements and the chromizing agent metal elements to quickly obtain the required penetration layer depth (in fact, chromizing does not only occur at the solid solution temperature); the solid solution nitriding is the nitriding of the metal product at the solid solution temperature. Taking stainless steel metal products as an example, according to the principle of thermal diffusion, the diffusion rate is proportional to the temperature. The solid solution temperature of stainless steel is mostly above 950°C. Heating the metal product to the solid solution temperature can effectively increase the diffusion rate of nitrogen. Further, taking austenitic stainless steel as an example, unlike the nitriding of traditional iron-based materials, nitriding is relatively difficult. In addition to considering that the stainless steel surface is very easy to produce a passive film that hinders the nitriding process, the stainless steel itself has a high content of Cr and Ni (strong nitride-forming elements). Under conventional nitriding methods, it takes longer to achieve a certain penetration layer thickness. Experiments have shown that using this solution, a nitrided layer thickness of 70μm to 110μm can be achieved on common austenitic stainless steel after 5 hours of solid solution nitriding. Conventional nitriding methods often require more than 80 hours to achieve this thickness. This solution provides a technical solution that ensures heat treatment efficiency.
[0068] At the same time, this solution aims to provide a technical solution that can effectively ensure the quality of surface heat treatment of austenitic stainless steel metal products. In the specific process steps designed in this solution, the surface chromizing step is set to be located before the surface nitriding step, and the surface chromizing step adopts slow cooling, while the surface nitriding step adopts rapid cooling. After the chromizing step is completed, slow cooling is preferably used: During the specific chromizing process, the product parts are in a solid solution state and at a high temperature. If the cooling rate is too fast, there are hidden dangers such as excessive stress in the chromized layer causing cracking and falling off. There is also a risk that the internal air pressure changes due to the rapid cooling rate, which may eventually increase the adhesion of powder and have an adverse effect on the part size. However, when slow cooling is implemented, conventional austenitic stainless steel is prone to intergranular corrosion. Therefore, this solution sets the nitriding step to be located after the chromizing step. By placing the chromized stainless steel at the solid solution temperature of the surface nitriding step, this harmful tendency can be effectively eliminated. Then, a rapid cooling method is adopted. While ensuring that the substrate does not have the tendency to intergranular corrosion, the rapid cooling can also effectively improve the hardness of the nitrided layer and prevent the hardness of the nitrided layer from decreasing due to the long-term maintenance of the solid solution temperature.
[0069] Example 2:
[0070] This embodiment is further defined on the basis of embodiment 1:
[0071] As a more specific application of the treatment method on austenitic stainless steel metal products, it is set as follows: the material of the metal product is austenitic stainless steel;
[0072] In the surface nitriding step, after the rapid cooling is completed, the temperature of the metal product is less than or equal to 400° C.
[0073] The slow cooling has a cooling rate of 30-35°C / h;
[0074] The cooling rate of the rapid cooling is 300-500℃ / h. In this solution, the temperature of the metal product at the end of rapid cooling is limited in order to shorten the duration of the intergranular corrosion sensitive temperature zone of austenitic stainless steel by rapid cooling, so as to ensure the structural composition of the surface nitride as much as possible (avoid nitrogen loss and structural changes), thereby ensuring the surface performance of the product. It is preferably set so that the metal product has a temperature below 200℃ after the rapid cooling is completed, so as to avoid oxidation or reduce the degree of oxidation during subsequent cooling in an open environment. The above-set slow cooling rate is a compromise between protecting the chromized layer, cooling efficiency, and intergranular corrosion tendency; the above rapid cooling rate is a compromise between protecting the chromized layer and cooling efficiency.
[0075] In this embodiment, three cooling methods, namely, slow cooling with furnace, high-purity argon gas cooling, and circulating water cooling, were used for comparative cooling tests. The Vickers hardness and metallographic structure of the nitrided parts obtained by different cooling methods were tested, and the data obtained were as follows:
[0076] Among them, F321 is Ni-Cr-Ti type austenitic stainless steel;
[0077] The following circulating water cooling method adopts a cooling rate of: 320~450℃ / h.
[0078] CN-1515 is a commonly used core structural material and is also a type of austenitic stainless steel.
[0079] For F321 material:
[0080]
[0081] For CN-1515 material:
[0082]
[0083]
[0084] In existing nitriding processes, ammonia is often used as the nitrogen-containing gas. However, this solution takes into account the following considerations: According to general nitriding rules, to ensure the nitriding treatment results (achieve high-precision nitriding control), the chemical potential of nitrogen in the nitriding atmosphere must be controlled. This is because general "gas-solid" interface nitriding requires a fixed nitrogen chemical potential on the product surface, which means that the composition inside the nitriding vessel should not change compared to the desired inlet gas composition. However, this solution requires nitriding at the solid solution temperature. In reality, ammonia will completely decompose at a pressure of 1 atm and a temperature above 350°C. The nitriding gas pressure used in this process and the solid solution temperature of stainless steel nitriding (far exceeding 350°C) determine that it is impossible to use ammonia for controllable nitriding. (If ammonia is used for nitriding, it will completely decompose in the heat and pressure environment of this process, and the nitrogen potential will decrease linearly as the nitriding progresses.) In other words, if ammonia is used for nitriding, it is impossible to accurately control the size of the nitrided layer and the uniformity of nitrogen diffusion on the product surface, which in turn affects the performance of the product.
[0085] Therefore, it is set as follows: in the surface nitriding step, the nitriding gas used is nitrogen. Using nitrogen will not cause the above problems: nitrogen will only decompose into free nitrogen atoms N under high temperature and high pressure conditions. ads , and then dissolves into the solid solution matrix (N ads →[N]), affected by the diffusion rate of the “gas-solid” interface, the excess N ads It will be recombined and absorbed on the surface of metal products, that is, the reverse effect of nitriding occurs (N ads +[N]→N2). It is precisely because of this counteraction (dynamic equilibrium) that the composition inside the nitriding vessel is virtually unchanged from the desired inlet gas composition, thereby ensuring nitriding quality. Furthermore, the diffusion rate of nitrogen in stainless steel is low. To achieve sufficient nitriding depth within an appropriate timeframe, this solution utilizes a solution temperature range. Within this temperature range, the nitrogen decomposition rate is extremely high, achieving equilibrium between the gas phase and the nitrogen dissolved into the surface during the dissolution process, resulting in an extremely high surface nitride content (≥99%).
[0086] As a further preferred embodiment of the above-mentioned nitrogen, it is set as follows: the purity of the nitrogen is greater than or equal to 99%. The nitrogen content in ordinary industrial nitrogen components is generally 92%, and the remaining components are mainly composed of O2, CO2, H2O, H2, SO2, etc. When industrial nitrogen is used for nitriding, oxidation and sulfidation may occur simultaneously. Among them, oxidation is the most dangerous because oxidation will cause the loss of chromium and nickel on the surface of metal products, which will have a negative impact on the corrosion resistance of stainless steel and even cause the metal products to be scrapped; while sulfidation will reduce the alloying elements on the surface of metal products, increase the brittleness of the surface after nitriding, and reduce its corrosion resistance. When nitriding is carried out using process nitrogen with a nitrogen component of 92%, the structure of the nitrided layer is observed under a metallographic microscope, and it is found that the surface nitrided layer has uneven granular structures, and the outer surface of the metal product is dark in color; under the measurement of a microhardness tester, the surface hardness is low, and a green oxidation color will appear locally. Using high-purity nitrogen with a nitrogen content of 99% or higher for nitriding under the same process results in a fine and uniform surface structure, a silver-gray surface color, and high surface hardness. This effectively avoids adverse effects such as oxidation and sulfidation. Furthermore, high-purity nitrogen promotes the structural transformation of metal products in the α phase due to nitrogen supersaturation, forming the γ phase, which improves surface hardness. Considering nitrogen cost and heat treatment quality, high-purity nitrogen with a nitrogen content of 99.999% is preferred.
[0087] At the same time, this embodiment provides a set of comparative experiments on the application of nitrogen in this solution.
[0088] The test used industrial nitrogen with a nitrogen purity of 92%, pure nitrogen of 98%, and high-purity nitrogen of 99.999% for nitriding test comparison. The chemical composition of 99.999% high-purity nitrogen is as follows:
[0089]
[0090] Three nitrogen gases of different purities were used to nitride the F321-based sample under the same process flow (slowly heating to 280°C-300°C, holding for 1.5 hours → heating to 600°C-620°C, holding for 2 hours → heating to 930°C-940°C, holding for 0.75 hours → heating to 1050°C-1100°C, holding for 4 hours → rapid cooling to below 200°C). The results are as follows:
[0091] (1) 92% industrial nitrogen: After nitriding and cooling, the surface of the parts is black with a layer of powdery attachments, the surface is partially green, and the surface has peeling and cracking. At the same time, after relevant physical and chemical tests, it is found that the nitriding layer is shallow and uneven, the outer surface of the nitriding layer is uneven, the thickness of the nitriding layer is about 50μm~70μm, the hardness of the nitriding layer is low, HV 0.1Approximately 400 to 460, the metallographic structure of the carburized layer is large, and the diffusion-affected layer has localized σ phases. After inspecting the overall airtightness of the device, it was determined that the 92% industrial nitrogen contained impurities such as O2, H2O, and H2, which caused surface oxidation and surface hydrogen bubbling during the high-temperature process. Simultaneously, the diffusion of impurity elements also affects [N] diffusion, resulting in undesirable results such as reduced carburized layer hardness, low nitride content, shallow carburized layer, and carburized layer brittleness. XRD testing of the carburized layer revealed that the nitride content in the carburized layer was only about 30%.
[0092] (2) 98% pure nitrogen: After nitriding and cooling, the surface of the part is dark gray, the surface color is uniform, and there is no peeling or cracking. Physical and chemical testing of the nitrided layer shows that the nitrided layer is relatively uniform, about 120μm to 140μm, and the hardness of the nitrided layer is relatively low, HV 0.1 About 570, the metallographic structure of the carburized layer is fine and uniform, and there is no σ phase structure in the diffusion-affected layer. After XRD analysis of the carburized layer, the nitride content of the carburized layer is about 60%;
[0093] (3) 99.999% high-purity nitrogen: After nitriding and cooling, the surface of the parts is bright silver-gray, the surface color is uniform, and there is no peeling or cracking. Physical and chemical testing of the nitrided layer shows that the nitrided layer is flat and uniform, about 130μm to 140μm, and the hardness of the nitrided layer is ideal, HV 0.1 About 880, the metallographic structure of the nitrided layer has fine and uniform particles, and there is no σ phase structure in the diffusion affected layer. After XRD analysis of the nitrided layer, the nitride content of the nitrided layer is as high as about 99.6%.
[0094] Three nitrogen gases of different purities were used to nitride CN-1515 substrates using the same optimal process flow. The results are as follows:
[0095] (1) 92% industrial nitrogen: After nitriding and cooling, the surface of the part is black with a layer of powdery attachments, the surface is partially green, and the surface has peeling, cracking and vein-like lines. After relevant physical and chemical tests, it is found that the nitriding layer is shallow and uneven, the outer surface of the nitriding layer is uneven, the thickness of the nitriding layer is about 20μm to 60μm, the hardness of the nitriding layer is low, HV 0.1 The density of the infiltrated layer was approximately 340, and the metallographic structure of the infiltrated layer had large particles, and the diffusion-affected layer had σ phase in some parts. After checking the overall airtightness of the device, it was determined that the 92% industrial nitrogen contained impurities such as O2, H2O, and H2, which caused oxidation and hydrogen corrosion during the high-temperature process, and at the same time affected the diffusion of [N], resulting in reduced infiltrated layer hardness, low nitride content, shallow infiltrated layer, and brittle and sensitive infiltrated layer. After XRD testing of the infiltrated layer, the nitride content in the infiltrated layer was only about 25%;
[0096] (2) 98% pure nitrogen: After nitriding and cooling, the surface of the part is dark gray, the surface color is uniform, and there is no peeling or cracking. Physical and chemical testing of the nitrided layer shows that the nitrided layer is relatively uniform, about 100μm to 120μm, and the hardness of the nitrided layer is relatively low, HV 0.1 About 420, the metallographic structure of the carburized layer is fine and uniform, and there is no σ phase structure in the diffusion-affected layer. After XRD analysis of the carburized layer, the nitride content of the carburized layer is about 73%;
[0097] 99.999% high purity nitrogen: After nitriding and cooling, the surface of the parts is bright silver-gray, the surface color is uniform, and there is no peeling or cracking. Physical and chemical testing of the nitrided layer shows that the nitrided layer is flat and uniform, about 130μm to 140μm, and the hardness of the nitrided layer is ideal, HV 0.1 About 590, the metallographic structure of the nitrided layer has fine and uniform particles, and there is no σ phase structure in the diffusion affected layer. After XRD analysis of the nitrided layer, the nitride content of the nitrided layer is as high as about 99.6%.
[0098] Example 3:
[0099] This embodiment is further defined on the basis of embodiment 1:
[0100] The material of the metal product is austenitic stainless steel;
[0101] In the surface chromizing step, chromium powder with a chromium content greater than or equal to 99% is used as a chromium supplying agent in the chromizing agent. In the prior art, the metal product is subjected to solution chromizing heat treatment by completing chromizing at the solution temperature, and the components of the chromizing agent generally include a chromium supplying agent, a filler, and a penetration promoter. Regarding the chromizing agent, the options include chromium powder, chromium oxide, ferrochrome powder, or any two or a mixture of the above three. From the perspective of the quality of the diffusion layer, chromium oxide and ferrochrome powder not only have higher impurity content (such as high carbon and silicon content in ferrochrome powder, impurities in chromium oxide generally include silicon oxide, carbon impurities accompanying the solution heat treatment of metal products will affect the corrosion resistance of the austenitic stainless steel surface, silicon is a ferrite-forming element, accompanying the solution heat treatment of metal products will affect the intergranular corrosion sensitivity of the austenitic stainless steel surface), but also affect the chromizing quality; compared with chromium powder, ferrochrome powder and chromium oxide generally have shallower diffusion layers and lower density under the same chromizing process.
[0102] In response to the above-mentioned problems, this solution, in combination with the component characteristics or material characteristics of austenitic stainless steel, provides a technical solution for using chromium powder as a chromium supply agent during the chromizing process of austenitic stainless steel, and is limited to: the chromium content in the chromium powder is greater than or equal to 99% (for those skilled in the art, this 99% is the mass fraction of chromium element: the proportion of chromium in the mass of the chromium powder). The technical solution aims to solve the following problems:
[0103] First, in the actual chromizing process, to control production costs, inert fillers (fillers) such as alumina are often used to increase the volume of the metal product so that the chromizing agent can embed itself within the metal. The quality of the halogen salt activator (penetration promoter) and the chromium powder (chromium supply agent) required to achieve the technical requirements for the chromizing layer must be carefully calculated. Too much activator can cause localized surface corrosion, similar to "mottling" on the metal surface; too little activator can lead to deviations in the thickness of the chromized layer, or even fail to meet technical requirements. The purity of the chromium powder actually affects the amount of chromium, so higher purity chromium powder facilitates precise control of the chromium content.
[0104] Secondly, chromium powders currently available on the market with a chromium content of 99% or less generally contain ferrite-forming elements such as titanium, niobium, molybdenum, and silicon. However, during the chromizing of austenitic stainless steel, since austenitic stainless steel itself contains ferrite-forming elements, the matrix easily forms a σ phase during the solid solution process. When the σ phase precipitates along the grain boundaries of austenitic stainless steel, it significantly affects the plasticity of the steel. Furthermore, since the σ phase in chromium-nickel austenitic stainless steel is a chromium-iron intermetallic compound with a high chromium content, when it forms at the grain boundaries, it also forms a certain chromium-depleted zone around it. This can cause localized intergranular corrosion in corrosive media, especially in the strongly oxidizing medium produced by the decomposition of the activator during the solid solution chromizing process. This intergranular corrosion sensitivity is even more pronounced, making the material particularly susceptible to pitting corrosion in Cl-containing media. In this solution, by selecting the chromium supply agent and using higher purity chromium powder, the infiltration of non-chromium elements during the chromizing process can be effectively reduced. By increasing the chromium content of the infiltrating elements in the steel, the purpose of reducing the impact of this intergranular corrosion on austenitic stainless steel is achieved.
[0105] Finally: If you choose chromium powder with a purity of 99.9-99.99% (mass fraction of chromium), you can keep the ferrite content in the normal austenitic stainless steel between 5-20%, which is beneficial for resisting intergranular corrosion. During the chromizing process, if the ferrite-forming element content in the chromizing agent is high, the ferrite-forming elements can diffuse into the metal products at high temperatures, affecting the value of this range to some extent.
[0106] The chromizing agent also includes a penetration enhancer, which is a mixture of ammonium chloride and ammonium iodide;
[0107] The mass of the permeation promoter accounts for 1-4% of the mass of the chromizing agent. Regarding the selection of the above permeation promoter, if only NH4I is used as the activator, since I- is less oxidizing than Cl-, its reaction ability with Cr element is limited, resulting in an uneven chromizing layer or even no chromizing layer in some parts;
[0108] If only NH4Cl is used as the chromizing agent, Cl- has strong oxidizing properties and is more reactive with Cr elements. However, it is found that the surfaces of metal products of different sizes produced by the furnace all have mottled patterns. Observation under a metallographic microscope shows that surface corrosion may have occurred, and the thickness of the chromized layer at the mottled pattern is significantly lower than that at the normal chromized area. The hardness of the mottled pattern and the normal chromized layer are measured using a microhardness tester, and it is found that there is a large gap between the two (the hardness and chemical composition of the mottled pattern are quite different from those of the normal chromized area, and the normal area has a HV 0.1 ≥1200, HV at the site of spotting 0.1 The temperature is generally around 800°C. Considering that the decomposition products of NH4Cl promote localized corrosion on the surface of metal products while promoting penetration, using only NH4I results in a thinner chromized layer at the same time, making it more difficult to promote penetration than using NH4Cl. Achieving the same chromized layer thickness requires a longer heating time, which can cause grain growth within the metal product and deteriorate its performance. Using a mixture of NH4Cl and NH4I as a penetration promoter can produce a more ideal chromized layer than using a single penetration promoter.
[0109] The proportion of the mass of the penetration promoter in the mass of the chromizing agent is set to limit the amount of halogen ions to ensure the quality of chromizing: it can effectively promote chromizing and will not damage the surface of the metal product due to excessive strong oxidizing halogen ions.
[0110] The components of the penetration enhancer are set as follows: the weight ratio of ammonium chloride to ammonium iodide in the penetration enhancer is (1.5-2.5):1. The above limitation on the weight ratio of the components in the penetration enhancer is intended to address the following concept: regarding compound stability, NH4Cl < NH4I, that is, in the early preheating stage of the chromizing temperature curve (such as before the second gradient section mentioned below), NH4Cl almost completely decomposes (NH4Cl almost completely decomposes at 337°C) into HCl + NH3 (both in the gas phase), and this decomposition reaction is reversible. In contrast, the decomposition products of NH4I are NH3, H2, and I2 (in the vapor phase), which is an irreversible reaction. The use of NH4Cl decomposition products in the early stage will inhibit the decomposition of NH4I. This not only ensures that NH4I can be completely decomposed later after the decomposition of NH4Cl is complete, but also avoids insufficient penetration enhancer: the chromizing reaction occurs not only on the surface of the metal product, but also on the inner surface of the chromizing container. The suppression of NH4I decomposition in the early stage ensures that there are sufficient halide ions in the atmosphere of the chromizing surface later. At the same time, the decomposition product of NH4Cl, HCl, can remove the passivation film and promote penetration through reaction.
[0111] The ratio of NH4Cl and NH4I is (1.5-2.5):1, which aims to ensure that there are sufficient halogen ions to promote the diffusion in the preheating stage and the high-temperature solid solution stage, so as to ensure that the thickness of the diffusion layer and the Cr content in the Cr diffusion layer are high enough: the actual chromization occurs at various moments of the temperature gradient curve, and the specific chromization locations include the inner wall of the chromization container, tooling and metal products. NH4Cl mainly supplies the chromization in the front part of the temperature gradient curve, and NH4I mainly supplies the halogen ions in the high-temperature zone in the back part of the temperature gradient curve. In the high-temperature stage, the Cr concentration on the chromized surface of the metal product is greater than the critical Cr concentration for the generation of only Cr2O3 (such as the Cr concentration is 10% in the range of 850℃-1050℃). The Cr concentration near the outer surface of the metal product is higher than that in the interior of the matrix, and the Cr element diffuses deeply. A combination of NH4Cl and NH4I in a ratio of (1.5-2.5):1 is selected for chromization. Taking advantage of the characteristics that the higher the temperature of I element, the greater the diffusion coefficient of chromization is and that it basically does not damage the surface of metal products, the chromization temperature can be increased to an upper limit of about 1150°C in order to obtain a chromized layer of sufficient size, a chromized layer with a higher chromium content, and a relatively short chromizing time.
[0112] In the ratio range of NH4Cl and NH4I, parameters such as 1:2, 1:1, 1.5:1, 2:1, 2.5:1, and 3:1 were selected. It was found that the chromized layers with ratios of 1:1, 1:2, and 3:1 became rough and uneven, with large differences in thickness and surface defects such as mottled patterns. Therefore, in order to improve the quality of chromizing, the ratio of NH4Cl:NH4I=(1.5~2.5):1 was adopted.
[0113] For better effect, the weight ratio of ammonium chloride to ammonium iodide is set to (1.8-2.1):1.
[0114] To reduce the effects of silicon, iron, and other elements on the surface of metal products, the chromizing agent also includes a filler, which is aluminum powder, aluminum oxide powder, or a mixture of aluminum and aluminum oxide powders, with a purity greater than or equal to 99%. Specifically, in practice, the filler may be aluminum powder alone, aluminum oxide powder alone, or a mixture of aluminum and aluminum oxide powders.
[0115] The specific chromizing agent composition can be: 99.99% high-purity chromium powder (45% to 70%), 99% high-purity alumina powder (30% to 55%), NH4Cl and NH4I mixed activator (1% to 4%), and sodium fluoride (0.5% to 1.5%), which are evenly mixed.
[0116] Example 4:
[0117] This embodiment is further defined on the basis of embodiment 1:
[0118] In both the surface chromizing step and the surface nitriding step, a heating method of performing gradient heating and gradient section heat preservation on the metal product is adopted.
[0119] In the above chromizing steps, a gradient temperature increase method is adopted to improve the quality of chromizing: for example, during the insulation process of the gradient section, not only the base temperature of the metal product is increased, but also the moisture on the surface of the metal product and in the chromizing agent is removed by drying, thereby preventing the subsequent decomposition products of the activator from causing acidic corrosion to the surface of the metal product; the activator is completely decomposed to release activated gas, and the residual air around the metal product and in the chromizing agent is removed to avoid oxidation of the metal product; at the subsequent solution chromizing temperature (due to the previous insulation, the temperature difference between the inside and outside of the metal product is smaller or the temperature is the same, and the time required for the chromized surface to be heated to the solution temperature is shorter), the relevant element replacement reaction can be carried out in the first time, thereby improving the chromizing efficiency and reducing the solution chromizing time, thereby reducing to a certain extent the adverse effects of grain growth caused by long-term solution.
[0120] In the above nitriding steps, gradient heating and heat preservation are adopted mainly because the heating of metal products is mainly carried out through secondary thermal radiation (such as: the first is heating furnace-air-tooling (nitriding container), and the second is: tooling-nitrogen-metal product). The heat transfer process causes a certain error between the temperature of the metal product and the temperature displayed by measuring instruments such as furnace thermocouples during heating. Therefore, one of the purposes of heat preservation after heating is to increase the base temperature of the metal product to facilitate nitrogen activation at the subsequent solution temperature: the relevant element replacement reaction at the solution temperature can be carried out at the first time, thereby improving the nitriding efficiency, reducing the solution time, and effectively avoiding the problem of poor performance of the nitriding layer caused by excessive grain growth and poor grain uniformity due to excessive solution time.
[0121] More specifically, in the surface chromizing step, the holding section in the heating curve includes a third gradient section and a fourth gradient section; preferably, the holding section also includes the first gradient section and the second gradient section provided before the first gradient section, and specifically, in chronological order:
[0122] The temperature of the first gradient section is 280-320°C;
[0123] The temperature value of the second gradient section is 550-650°C;
[0124] The temperature value of the third gradient section is 900-950°C;
[0125] The temperature value of the fourth gradient section is 1050-1150°C;
[0126] In the surface nitriding step, the holding section in the heating curve includes the seventh gradient section and the eighth gradient section; preferably, it is set to also include the fifth gradient section and the sixth gradient section arranged before, specifically in chronological order:
[0127] The temperature value of the fifth gradient section is 280-350°C;
[0128] The temperature value of the sixth gradient section is 500-650°C;
[0129] The temperature of the seventh gradient section is 850-980°C;
[0130] The temperature value of the eighth gradient section is 1000-1150°C.
[0131] In the above nitriding step scheme, the typical process can be to slowly heat up to 280℃~300℃, keep warm for 1~3h → heat up to 550℃~620℃, keep warm for 1~3h → heat up to 900℃~950℃, keep warm for 0.5~1h → keep warm at 1030℃~1100℃ for 3~6h (determined by the thickness requirement of the nitriding layer) → quickly cool to 200℃.
[0132] In the above chromizing step scheme, in addition to further increasing the base temperature of the metal product at each stage, the first gradient stage is the stage of drying the metal product and the chromizing agent; the second gradient stage is the stage of complete decomposition of the activator; and the third gradient stage is intended to achieve:
[0133] 1. Stabilization of the base material of metal products: After heating to 900-950℃ and keeping it at 900-950℃, the C remaining in the austenite can fully react with Ti, Nb, etc. and precipitate in the form of TiC and NiC, so that C cannot form Cr precipitation along the grain boundary with Cr in the subsequent fourth gradient section. 23 C6 carbide can prevent intergranular corrosion in subsequent processes.
[0134] 2. Improve the temperature uniformity of the base material, reduce the temperature difference between the core and outer surface of the metal product and the heating furnace temperature (the heating furnace is used to heat the chromizing container), and reduce the time it takes for the metal product to reach the chromizing temperature due to multiple heat transfers: the heating time from the end of the third gradient section to the fourth gradient section; the time difference between the chromized surfaces at different positions or the chromized surfaces at different positions reaching the solid solution temperature, to ensure that the quality of the chromized layer is accurately controllable.
[0135] In this scheme, the fourth gradient section is the solid solution chromizing temperature stage, which is used to complete chromizing at the austenite solid solution temperature. The temperature range of 1050-1150℃ is used for insulation. The ion exchange between the base material elements and the metal elements of the chromizing agent is active, which can ensure the depth of the diffusion layer.
[0136] The above content is a further detailed description of the present invention in conjunction with specific preferred embodiments, and the specific embodiments of the present invention cannot be considered to be limited to these descriptions. For those skilled in the art to which the present invention belongs, other embodiments derived without departing from the technical solution of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for heat treating the surface of a metal product, comprising a surface nitriding step and a surface chromizing step of the metal product, characterized in that: The surface chromizing step is located before the surface nitriding step; In the surface chromizing step, the chromizing stage includes a solution chromizing stage of chromizing at a solution temperature of the metal product, and after the solution chromizing stage is completed, a slow cooling method is adopted in the cooling process of the metal product; In the surface nitriding step, the nitriding stage includes a solid solution nitriding stage in which nitriding is performed at a solid solution temperature of the metal product. After the solid solution nitriding stage is completed, a rapid cooling method is adopted in the cooling process of the metal product; The material of the metal product is F321 austenitic stainless steel or CN-1515 austenitic stainless steel; In the surface nitriding step, after the rapid cooling is completed, the temperature of the metal product is less than or equal to 400° C.; The slow cooling rate is 30-35°C / h; The rapid cooling adopts circulating water cooling, and the cooling rate is: 320~450℃ / h; In the surface nitriding step, the nitriding gas used is nitrogen; The purity of the nitrogen is greater than or equal to 99%; In both the surface chromizing step and the surface nitriding step, a heating method of gradient heating and gradient section heat preservation is adopted for the metal parts; In the surface chromizing step, the heat preservation section in the heating curve includes a third gradient section and a fourth gradient section; The temperature value of the third gradient section is 900-950°C; The temperature value of the fourth gradient section is 1050-1150°C; In the surface nitriding step, the heat preservation section in the heating curve includes the seventh gradient section and the eighth gradient section; The temperature value of the seventh gradient section is 850-980°C; The temperature value of the eighth gradient segment is 1000-1150°C.
2. The method for heat treatment of metal product surface according to claim 1, characterized in that: In the surface chromizing step, chromium powder with a chromium content greater than or equal to 99% is used as a chromium supply agent in the chromizing agent.
3. The method for heat treatment of metal product surface according to claim 2, characterized in that: The chromizing agent also includes a penetration enhancer, which is a mixture of ammonium chloride and ammonium iodide; The mass of the penetration enhancer accounts for 1-4% of the mass of the chromizing agent.
4. The method for heat treatment of metal product surface according to claim 3, characterized in that: In the penetration enhancer, the weight ratio of ammonium chloride to ammonium iodide is: (1.5-2.5):
1.
5. The method for heat treatment of metal product surface according to claim 2, characterized in that: The chromizing agent also includes a filler, which is aluminum powder, aluminum oxide powder, or a mixture of aluminum powder and aluminum oxide powder with a purity greater than or equal to 99%.
Citation Information
Patent Citations
Chromizing method for austenitic stainless steel, chromizing agent and part
CN113604775A